Development of Low-Noise / Low-Power Preamplifier for the Readout of Inorganic Scintillators and their Mass Production Test System. (13th February 2015) - Keshelashvili, I; Erni, W; Müller, F; Steinacher, M; Krusche, B
Abstract: The development of the preamplifer and all test procedures done by our group during the past several years at the University of Basel will be discussed. In addition, we present the results from the testing of the first 1500 channels of the preamplifiers for the Crystal Barrel experiment using a specially developed automatized test system.